Decoupled Dynamic Control of Unicycle Robot Using Integral Linear Quadratic Regulator and Sliding Mode Controller. (2016) - Mohan, Shweda; Nandagopal, J.L.; Amritha, S.
Abstract: Unicycle robot is a non-holonomic, non-linear, static unbalance system that has the minimal number of point contact to the ground, therefore it is a perfect platform for researchers to study motion and balance control. This paper focuses on the dynamic modeling of unicycle robot. Two concepts used for modeling unicycle robot are: reaction wheel pendulum and inverted pendulum. The pitch axis is modeled as inverted pendulum and roll axis is modeled as reaction wheel pendulum. The unicycle yaw dynamics is not considered which makes derivation of dynamics relatively simple. For the roll controller, sliding-mode controller has been adopted and optimal methods are used to minimize switching-function chattering. For pitch controller, a Linear Quadratic Regulator controller has been implemented to drive the unicycle robot to follow the desired velocity trajectory.